METAFISIKA SIMBOL KERIS JAWA - Nurhadi Siswanto (Jurnal Filsafat "WISDOM", 2012)
Essential issue in the study of the metaphysics of symbol is based on two main questions: (1) is a symbol immanent in human (and limitedly rooted in the human spirit) or symbol is also rooted to the transcendent (which address the human and his life)?; and (2) is a symbol just has horizontal dimension or vertical dimension as well?The creation of keris is a mixture of desires, hopes, goals, and desired benefits from the buyer if the dagger with a sense, initiative and creativity embodied in the master symbols at luk, dhapur, and pamor. The master in the making process, entered the dimensions of the symbols commonly applicable in the Javanese community. Javanese keris analyzed from the point of the symbol, can be concluded that the symbol visible at the class of ordinary Javanese (the public) is more vertical-transcendental, and the special group (the intellectuals) Javanese symbol doubles the vertical dimension-transcendental, as well as horizontal-immanent, while the new class (the keris is considered as art), Javanese symbolism over the horizontal dimension-immanent.